Renewable energy and power supply challenges for rural regions - Kharchenko, Valeriy, 1938-; Vasant, Pandian (IGI Global, 2019)
"This book examines theoretical and experimental research in the field of renewable energy sources. It explores the application of electrical technologies in agro-engineering processes that provide increased yields, increased productivity, and improved working conditions. It also highlights the issues of the energy supply of agricultural production and the household aspects of life in rural areas"--